2006
DOI: 10.1359/jbmr.060105
|View full text |Cite
|
Sign up to set email alerts
|

Cortical PQCT Measures Are Associated With Fractures in Dialysis Patients

Abstract: To determine if pQCT could identify HD patients with fractures, we conducted a cross-sectional study in 52 men and women on HD. We found that cortical, but not trabecular, pQCT measures were associated with fractures.Introduction: Fractures are common in hemodialysis (HD) patients, yet DXA is inconsistently associated with fractures. One explanation for this lack of association may be that HD patients have a selective decrease in cortical density not identified by standard DXA. Materials and Methods: We used p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
124
4
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 162 publications
(135 citation statements)
references
References 31 publications
4
124
4
3
Order By: Relevance
“…The authors describe a general reduction of cortical volumetric bone mineral density (vBMD), stable trabecular vBMD, and a significant relationship between bone loss and dialysis vintage. With pQCT, a significant association with fracture was found for lower Dcort and CtTh, but not for Dtrab or DXA measurements at the lumbar spine and femur (8). An important finding reported here is that poor trabecular microarchitecture is associated with bone fractures in dialysis patients.…”
Section: Discussioncontrasting
confidence: 41%
See 2 more Smart Citations
“…The authors describe a general reduction of cortical volumetric bone mineral density (vBMD), stable trabecular vBMD, and a significant relationship between bone loss and dialysis vintage. With pQCT, a significant association with fracture was found for lower Dcort and CtTh, but not for Dtrab or DXA measurements at the lumbar spine and femur (8). An important finding reported here is that poor trabecular microarchitecture is associated with bone fractures in dialysis patients.…”
Section: Discussioncontrasting
confidence: 41%
“…pQCT, which does not permit assessment of trabecular microarchitecture, has been used previously in hemodialysis patients (8,16,17). The authors describe a general reduction of cortical volumetric bone mineral density (vBMD), stable trabecular vBMD, and a significant relationship between bone loss and dialysis vintage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent cross-sectional ROC study in 52 adults on maintenance hemodialysis demonstrated that reductions in pQCT measures of cortical bone in the radius were strongly predictive of vertebral and fragility fractures, whereas pQCT trabecular vBMD and DXA areal BMD were not [59]. Table 2 illustrates the marked differences in the odds of fracture and AUC at each site.…”
Section: Dxa and Pqct Receiver Operating Characteristic Curves In Ckdmentioning
confidence: 99%
“…The loss of bone structural integrity could also be explained by lead's activation of the peroxisome proliferator-activated receptor (PPAR)-γ pathway, leading to preferential differentiation of mesenchymal stem cells to adipocytes rather than to osteocytes [26]. Cortical thickness was the primary variable that showed any effect due to bone lead, and is also one of the most clinically impacted structural outcomes previously reported to relate directly to fracture risk [27,28]. Trabecular bone exhibits a higher turnover than cortical bone.…”
Section: Discussionmentioning
confidence: 99%